Synodus autumnus, a new species of lizardfish (Aulopiformes, Synodontidae) from the Indo-Pacific region, and a reassessment of distributional records of Synodus rubromarmoratus - Ryusei Furuhashi; Hiroyuki Motomura (ZooKeys, 2025)
The Indo-Pacific lizardfish Synodus autumnus sp. nov. (Aulopiformes, Synodontidae) is morphologically distinct from all other nominal species of Synodus, and is described as new. It is characterized by the following combination of characters: dorsal-fin rays 11–13; anal-fin rays 8–10; lateral-line scales 49–51; scale rows above lateral line 3.5; scale rows below lateral line 4.5; vertebrae 49–52; anterior gill rakers 22–29; peritoneal spots 0–5; anterior palatine teeth in a discrete group, longer than posterior palatine teeth; anterior nostril flap long, broad, leaf-like, extending above and behind posterior margin of posterior nostril when laid back; posterior process of pelvic girdle wide; posterior part of preopercle scaled; body with 5 reddish saddle-like blotches; and lateral surface below lateral line with a straight row of brown blotches when fresh. The new species is similar to Synodus binotatus Schultz, 1953 and Synodus rubromarmoratus Russell & Cressey, 1979, but these species differ in having 52–56 and 53–55 lateral-line scales, respectively. In addition, S. binotatus has blotches below the lateral line in a zigzag pattern, and S. rubromarmoratus has anterior and posterior palatine teeth similar in length, 14–25 teeth on the tongue, and 0–5 peritoneal spots. No color pattern differences were apparent between the new species and S. rubromarmoratus, making differentiation between the two species in underwater photographs impossible; consequently, underwater photographs and unsupported catalog records were excluded from the reassessment of each species’ distribution. Examination of specimens reported as S. rubromarmoratus revealed that the true S. rubromarmoratus has been collected only in Australian waters, whereas S. autumnus sp. nov. is widely distributed in the eastern Indian and Pacific oceans.